Implementasi Peraturan Daerah Nomor 36 Tahun 2011 Tentang Izin Mendirikan Bangunan Dalam Peningkatan Pendapatan Asli Daerah Kota Gorontalo - Noviyanti Tue (Institute Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2019)
The Research Aims To Investigate (1) Strategi Of Regional Regulation Implentation No. 26 Of 2011 About Building Permit Improvement Of Local Government Revenue Of Gorontalo City (2) Factor Determining Succes Of Regional Regulation Implementation No. 36 Of 2011 About Bulding Permit And Improvement Of Local Government Revenue Of Gorontalo City (3) Optimization Effort Of Regional Regulation Implementation No. 36 Of 2011 About Building Permit Improvement Of Local Government Revenue. It Applies Qualitative Approach By Having Primary Data As Data Source And They Are Obtained Trhough Interview. Technique Of Analyzing The Data Applies Miles & Huberman Interactive Model. Research Finding Are (1) Overall, Implementation Of Regional Regulation No. 36 Of 2011 About Building Permit In Improvement Of Local Government Revenue Of Gorontalo City Has Been Good, Yet An Improvement Is Required Particulary At Its Service That May Decrease People Obedience As Well As Well As The Sanction Should Be More Assertive To Create Deterrent Effect. (2) Strategy In The Implementation Of Regional Regulation No.36 Of 2011 About Building Permit In Improvement Of Local Government Revenue Of Gorontalo City Are Stable Strategy If The Service, Retribution Collection, Supervision And Sanction Impact Retribution Of Building Permit Paying Obedience And Diversification Strategy If The Service, Retribution ,Collection Supervision, And Sanction Are Not Optium. (3) Facto Determining Succes Implementation Of Regional Regulation No. 36 Of 2011 About Building Permit In Improvement Of Local Government Revenue Off Gorontalo City Comprise Comunication, Resource, Disposition, Or Atitude Of Implementer And Structure Of Bureaucracy.(4) Problem On Implementation Of Regional Regulation No.36 Of 2011 About Building Permit Improvement Of Local Government Revenuecan Be Solved Through Two Ways Namely Intensification And Extensification.